2019
DOI: 10.1021/acsomega.8b02823
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Salinity Sensing Using Long-Period Fiber Gratings Functionalized with Layer-by-Layer Hydrogels

Abstract: Rapid, accurate, and real-time measurements of ocean salinity are of great importance for a host of scientific, commercial, and defense applications. We demonstrate a highly sensitive, fast-responding fiber-optic salinity sensor that integrates long-period fiber gratings (LPFGs) with ionic strength-responsive hydrogel. The submicron-thick hydrogel was synthesized via layer-by-layer electrostatic assembly of partially quaternized poly(4-vinylpyridine) (qP4VP) and poly(acrylic acid), followed by chemical cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 52 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…Using a diazide cross-linker, Shi and co-workers fabricated poly­(allylamine hydrochloride) (PAH)/catalase multilayer hydrogels that showed enhanced chemical stability for cell proliferation . In our group, we have shown that multilayer networks of poly­( N -vinylcaprolactam) undergo reversible shrinkage with temperature, while poly­(4-vinylpyridine) (PVP) and PMAA hydrogels reversibly swell up to 20-fold with pH and can be utilized for amino acid sensing. A recent study by Yang et al showed that PVP-based hydrogels can be used as salinity sensors . Thus, owing to their unique swelling behavior, multilayer hydrogels possess great potential for a wide range of applications, from sensing and controlled drug delivery to antibacterial and anti-icing coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a diazide cross-linker, Shi and co-workers fabricated poly­(allylamine hydrochloride) (PAH)/catalase multilayer hydrogels that showed enhanced chemical stability for cell proliferation . In our group, we have shown that multilayer networks of poly­( N -vinylcaprolactam) undergo reversible shrinkage with temperature, while poly­(4-vinylpyridine) (PVP) and PMAA hydrogels reversibly swell up to 20-fold with pH and can be utilized for amino acid sensing. A recent study by Yang et al showed that PVP-based hydrogels can be used as salinity sensors . Thus, owing to their unique swelling behavior, multilayer hydrogels possess great potential for a wide range of applications, from sensing and controlled drug delivery to antibacterial and anti-icing coatings.…”
Section: Introductionmentioning
confidence: 99%
“…42−44 A recent study by Yang et al showed that PVP-based hydrogels can be used as salinity sensors. 45 Thus, owing to their unique swelling behavior, multilayer hydrogels possess great potential for a wide range of applications, from sensing and controlled drug delivery to antibacterial and antiicing coatings. Yet, there is a significant lack of knowledge concerning the internal organization of multilayer networks, which limits our understanding of the relationship between the network structure and film properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The first idea of polymer crosslinking was introduced by Charles Goodyear in 1839, aiming for tougher and longerlasting sulfur-crosslinked rubber properties than uncrosslinked rubber [20]. Crosslinking during hydrogel fabrication creates the three-dimensional polymeric network [21] and prevents the dissolution of polymer chains in a solvent [22]. The concentration of the crosslinker significantly affects the swelling capacity of the hydrogel, whereby a higher concentration of crosslinker will result in lower swelling capacity and vice versa [10][11][12].…”
Section: Hydrogel Production and Crosslinking Methodsmentioning
confidence: 99%
“…Therefore, more and more researchers began to apply stimuli-responsive materials to the field of optical sensing. Stimuli-responsive optical waveguide materials are increasingly used in the field of optical sensings, such as detecting pH, temperature, enzyme, small molecules, , ion concentration, , etc. Yetisen et al report a phenylboronic acid-functionalized glucose-sensitive hydrogel flexible optical waveguide that can implement continuous glucose monitoring in vivo (Figure D) .…”
Section: Soft and Stretchable Optical Waveguide And Novel Applicationsmentioning
confidence: 99%